Abstracts Accepted for Publication 2019
DOI: 10.1136/annrheumdis-2019-eular.3745
|View full text |Cite
|
Sign up to set email alerts
|

Ab0736 gender Influence on Treatment Effectiveness in Psoriatic Arthritis

Abstract: BackgroundGender has been lately suggested as influential in the response to treatment with biological drugs in spondyloarthritis, such as psoriatic arthritis (PsA). However, data about the association between gender and treatment response in axial PsA (axPsA) or peripheral PsA (pPsA) are scarce.ObjectivesTo analyze the association between gender and clinical response to biological therapy in patients with axPsA and pPsA.MethodsAn observational cohort study was conducted, prospectively collecting data from 108… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Of the included studies, 11 were prospective cohort or observational studies, [13][14][15][16][17][18][19][20][21][22][23] including 1 post hoc analysis of a prospective observational study. 15 In total, 5 included studies were retrospective observational studies, [24][25][26][27][28] and 9 were cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the included studies, 11 were prospective cohort or observational studies, [13][14][15][16][17][18][19][20][21][22][23] including 1 post hoc analysis of a prospective observational study. 15 In total, 5 included studies were retrospective observational studies, [24][25][26][27][28] and 9 were cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37] Only 1 study was reported as a qualitative research study 38 and, finally, 1 study was reported as a population-based cohort study. 39 Population size varied greatly across the included studies, from 108 patients 14 to 8677 patients 25 (Supplementary Table S7, available with the online version of this article). Quality assessment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A real-world analysis of patients with PsA using data from the Corrona registry showed patients who discontinued a new TNFi treatment by the first follow-up visit were more likely to be women with higher disease activity and worse PROs than patients who continued with the defined index treatment; however, the difference between men and women was only significant among TNFi-experienced patients [ 25 ]. In a prospective observational study of 108 patients treated with biological therapy (93% TNFi and 7% IL-17i), male sex was associated with a higher rate of response to biological treatment in both axial PsA and peripheral PsA; however; in a real-world setting, secukinumab improved disease activity and depressed mood in both men and women with PsA, although women demonstrated an overall higher disease burden [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%